Colloquial Speech of University Students Utterance - Lubis, Fauziah Khairani; Bahri, Syamsul (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
The purpose of this study is to know more about the use of colloquial speech that grows and develops in the youth generation particularly college students. The researcher applied a qualitative descriptive research method with the theory of types of colloquial speech according to Yule (2010) as a detailed explanation. The research subject was students majoring in the English department at the language and art faculty, State University of Medan. Participant observation and interviews were the technique in collecting data. The result showed that from fifty samples of data, there were only seven of nine types shown by students namely, coinage, borrowing, compounding, blending, clipping, acronyms, and multiple processes. College students tend to show the use of coinage, blending, and acronyms. Communicating using colloquial speech or slang can help the user look more relaxed, cooler, confident, and not left behind. The informants adopt colloquial speech from online media even surrounding where they lived and applied it to the daily conversation with groups of friends.